The effect of population characteristics on water use and Conservation from pollution in the city of Unaizah: Geographical study - Alkushipan, Haifa Ali (Journal of natural sciences, life and applied sciences, 2021)
The objective of this study was to determine the physical, chemical and bacterial characteristics of drinking water in the public network, ground reservoirs and the internal household network and compare them with the natural and chemical drinking water characteristics in accordance with the Saudi standards. Also, to determine the differences in these characteristics between the public network and the terrestrial tanks reservoirs and internal household network of the city of Onaizah neighborhoods that were selected for the study which included Qadisiyah, Sulaymaniyah, King Khaled, Downtown, Airport, Park, Malihah, Salam and also to reveal the most important variables that negatively affect the characteristics of drinking water. The study showed that there were no differences in drinking water chemical and the physical characteristics in the public network as compared to the Saudi standards, and it was also found that there were differences in drinking water characteristics in the public network, the terrestrial tanks and the internal household network. Similarly, there was spatial variation in drinking water characteristics between the various studied neighborhoods. The study showed that the age of the main public network has caused significant difference in the values of total hardness, total soluble salts, chlorides, and calcium concentrations in the water of the network. The distance between the main pumping tank and the terrestrial tanks did not affect the various values of most of the studied characteristics with the exception of sulphates. The results also showed higher pH values for drinking water in the neighborhoods where the sewage network is found as compared to areas that are lacking sewage network. It was also found that the frequency of cleaning the tank and the distance between the drinking water tank reservoir and the sewage tank is one of the most important variables that affect the drinking water characteristics in the domestic reservoirs, where it had affected the variation in the values of total hardness, total soluble salts, chlorides, sulphates, calcium concentrations, while the type of domestic water network material affected the differences in the values of total soluble salts, chlorides, sulfates concentration as well as electrical conductivity of the water in the domestic network. The study also pointed to the positive impact of the increase in the monthly income of the resident of the house and his ownership of the house. This has increased their attention to the ground reservoir tanks cleaning and thus the quality of drinking water.